Recovery of Vestibular Ocular Reflex Function and Balance Control after a Unilateral Peripheral Vestibular Deficit - Allum, John (Frontiers in Neurology, 2012)
This review describes the effect of unilateral peripheral vestibular deficit (UPVD) on balance control for stance and gait tests. Because a UPVD is normally defined based on vestibular ocular reflex (VOR) tests, we compared recovery observed in balance control with patterns of recovery in VOR function. Two general types of UPVD are considered; acute vestibular neuritis (AVN) and vestibular neurectomy. The latter was subdivided into vestibular loss after cerebellar pontine angle tumor surgery during which a vestibular neurectomy was performed, and vestibular loss following neurectomy to eliminate disabling Ménière’s disease. To measure balance control, body-worn gyroscopes, mounted near the body’s center of mass (CoM), were used. Measurement variables were the pitch (anterior–posterior) and roll (lateral) sway angles and angular velocities of the lower trunk/pelvis. Both patient groups showed balance deficits during stance tasks on foam, especially with eyes closed when stable balance control is normally highly dependent on vestibular inputs. Deficits during gait were also present and were more profound for complex gait tasks such as tandem gait than simple gait tasks. Major differences emerged between the groups concerning the severity of the deficit and its recovery. Generally, the effects of acute neuritis on balance control were more severe but recovered rapidly. Deficits due to vestibular neurectomy were less severe, but longer lasting. These results mostly paralleled recovery of deficits in VOR function. However, questions need to be raised about the effect on balance control of the two modes of neural plasticity occurring in the vestibular system following vestibular loss due to neuritis: one mode being the limited central compensation for the loss, and the second mode being some restoration of peripheral vestibular function. Future work will need to correlate deficits in balance control during stance and gait more exactly with VOR deficits and carefully consider the differences between insufficient central compensation compared to inadequate peripheral restoration of function.